Local therapy with CpG motifs in a murine model of allergic airway inflammation in IFN-β knock-out mice - Navikas Vaidrius (Respiratory Research, 2005)
Abstract Background CpG oligodeoxynucleotides (CpG-ODN) are capable of inducing high amounts of type I IFNs with many immunomodulatory properties. Furthermore, type-I IFNs have been proposed to play a key role in mediating effects of CpG-ODN. The precise role of IFN-β in the immunomodulatory effects of CpG-ODN is not known. Objective Here, we aimed to elucidate the role of IFN-β in the anti-allergic effect of CpG motifs. Methods We assessed the immune response in OVA-primed/OVA-challenged IFN-β knockout (-/-) mice compared to wild type (WT) control, after intranasal and systemic treatment with synthetic CpG motifs. Results Vaccination with CpG-ODN reduced the number of cells in airways of OVA-sensitized WT but not IFN-β-/- mice. Although airway eosinophilia was reduced in both treated groups, they were significantly higher in IFN-β-/- mice. Other inflammatory cells, such as lymphocytes and macrophages were enhanced in airways by CpG treatment in IFN-β-/- mice. The ratio of IFN-γ/IL-4 cytokines in airways was significantly skewed to a Th1 response in WT compared to IFN-β-/- group. In contrast, IL-4 and IgE were reduced with no differences between groups. Ag-specific T-cell proliferation, Th1-cytokines such as IFN-γ, IL-2 and also IL-12 were significantly lower in IFN-β-/- mice. Surprisingly, we discovered that intranasal treatment of mice with CpG-ODN results in mild synovitis particularly in IFN-β-/- mice. Conclusion Our results indicate that induction of Th1 response by therapy with CpG-ODN is only slightly and partially dependent on IFN-β, while IFN-β is not an absolute requirement for suppression of airway eosinophilia and IgE. Furthermore, our finding of mild synovitis is a warning for possible negative effects of CpG-ODN vaccination.